The Real Ideal: Misestimation of Body Mass Index - Aniulis, Ellie; Moeck, Ella K.; Thomas, Nicole A.; Sharp, Gemma (Frontiers in Global Women's Health, 2022)
In Western cultures, the ideal body for women is thin and toned. Idealization of thinness has led many women to desire bodies with an underweight body mass index (BMI). The present study investigated women's knowledge of BMI, particularly relating to their own body ideals, to determine whether women knowingly idealize bodies categorized as “underweight.” In August 2020, one-hundred and forty-seven US women aged 18 to 25 completed two online tasks in a repeated-measures design. First, participants estimated the BMIs of a series of bodies. Then, participants selected representations of their own and ideal bodies from a figure rating scale and estimated the BMIs of their selections. Participants generally mis-estimated the BMI of bodies, but did so to a greater extent when viewing bodies as an extension of their own, i.e., following the figure rating scale task. Further, if participants selected an underweight or overweight ideal body, they were likely to estimate this body was within a “normal” weight BMI range, demonstrating that women who idealize underweight–or overweight–bodies do so unknowingly. These findings suggest misperceptions of women's own ideal body size are often greater than misperceptions of other bodies, potentially driving the tendency to idealize underweight bodies.